BAG3 induces α‐SMA expression in human fibroblasts and its over‐expression correlates with poorer survival in fibrotic cancer patients. Issue 1 (6th November 2021) - De Marco, Margot; Del Papa, Nicoletta; Reppucci, Francesca; Iorio, Vittoria; Basile, Anna; Falco, Antonia; Iaccarino, Roberta; Brongo, Sergio; De Caro, Francesco; Capunzo, Mario; Turco, Maria Caterina; Rosati, Alessandra; et al.
Abstract: Hypoxia and angiogenesis in solid tumors are often strictly linked to the development of fibrotic tissues, a detrimental event that compromises the antitumor immunity. As a consequence, tumor aggressiveness and poor patient prognosis relate to higher incidence of tissue fibrosis and stromal stiffness. The molecular pathways through which normal fibroblasts are converted in cancer‐associated fibroblasts (CAFs) have a central role in the onset of fibrosis in tumor stroma, thus emerging as a strategic target of novel therapeutic approaches for cancer disease. Several studies addressed the role of BAG3 in sustaining growth and survival of cancer cell and also shed light on the different mechanisms in which the intracellular protein is involved. More recently, new pieces of evidence revealed a pivotal role of extracellular BAG3 in pro‐tumor cell signaling in the tumor microenvironment, as well as its involvement in the development of fibrosis in tumor tissues. Here we report further data showing the presence of the BAG3 receptor (Interferon‐induced transmembrane protein [IFITM]‐2) on the plasma membrane of normal dermal fibroblasts and the activity of BAG3 as a factor able to induce the expression of α‐smooth muscle actin and the phosphorylation of AKT and focal adhesion kinase, that sustain CAF functions in tumor microenvironment. Furthermore, in agreement with these findings, bag3 gene expression has been analyzed by high throughput RNA sequencing databases from patients‐derived xenografts. A strong correlation between bag3 gene expression and patients' survival was found in several types of fibrotic tumors. The results obtained provide encouraging data that identify BAG3 as a promising therapeutic target to counteract fibrosis in tumors.